MiR-203 Involves in Neuropathic Pain Development and Represses Rap1a Expression in Nerve Growth Factor Differentiated Neuronal PC12 Cells. Issue 1 (January 2015) - Li, Haixia; Huang, Yuguang; Ma, Chao; Yu, Xuerong; Zhang, Zhiyong; Shen, Le
<x xml:space="preserve">Abstract</x> Objectives: Although microRNAs (miRNAs) have been shown to play a role in numerous biological processes, their function in neuropathic pain is not clear. The rat bilateral sciatic nerve chronic constriction injury (bCCI) is an established model of neuropathic pain, so we examined miRNA expression and function in the spinal dorsal horn in bCCI rats. Methods: Microarray and real-time polymerase chain reaction were used to examine the expression of miRNA in nerve system of bCCI rats, and the targets of miRNA were predicted by bioinformatic approaches. The function of specific miRNA was estimated through the methods of gene engineering. Results: This study revealed substantially (∼10-fold) decreased miR-203 expression in the spinal dorsal horns but not the dorsal root ganglions, hippocampus, or anterior cingulate cortexes of bCCI rats. Rap1a protein expression was upregulated in bCCI rat spinal dorsal horns. We further verified that miR-203 directly targeted the 3′-untranslated region of the rap1a gene, thereby decreasing rap1a protein expression in neuron-like cells. Discussion: Rap1a has diverse neuronal functions and their perturbation is responsible for several mental disorders. For example, Rap1a/MEK/ERK is involved in peripheral sensitization. These data suggest a potential role for miR-203 in regulating neuropathic pain development, and Rap1a is a validated target gene in vitro. Results from our study and others indicate the possibility that Rap1a may be involved in pain. We hope that these results can provide support for future research into miR-203 in gene therapy for neuropathic pain.